Pengaruh Media Interaktif Google Sites Berbasis CRT terhadap Hasil Belajar Kognitif dan Sikap Menghormati Siswa - Ria Apriani; Osa Juarsa; Neza Agusdianita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effect of Google Sites –based interactive media using a Culturally Responsive Teaching (CRT) approach on cognitive learning outcomes and students’ attitudes toward respecting cultural diversity among fifth-grade elementary school students, as well as to examine the correlation between these two variables. The study employed a quantitative approach with a quasi-experimental method using a Matching-Only Pretest–Posttest Control Group Design. The research sample consisted of class VA as the experimental group (20 students), class VB as the control group (20 students), and class VIA as the instrument try-out class. The research instruments included an essay test to measure cognitive learning outcomes and an observation sheet to assess attitudes toward respecting cultural diversity. Data were collected through pretests, posttests, and attitude questionnaires, while data analysis involved descriptive analysis, prerequisite testing, Independent Samples t-test, and Pearson correlation analysis. The results indicate that the use of Google Sites –based interactive media with a CRT approach has a significant effect on students’ cognitive learning outcomes and their attitudes toward respecting cultural diversity. Furthermore, a strong and positive correlation was found between cognitive learning outcomes and attitudes toward respecting cultural diversity. These findings suggest that integrating digital media with a CRT approach is effective in teaching Pancasila Education at the elementary school level.